Developing a theory driven and evidence based targeted intervention for the primary prevention of PTSD - Skeffington, Petra May (Curtin University, 2015)
Some professions, by their nature, will be exposed to trauma. Fire and emergency workers have abnormally high rates of stress related negative outcomes such as Post-traumatic Stress Disorder (PTSD). This research project explored the possibility of teaching resilience to adults in high-trauma professions. A systematic review consolidated current research relevant to the primary prevention of PTSD and cross-sectional surveys of the general population and DFES (Department of Fire and Emergency Services) workers in Australia informed the development of a theory driven and evidence based training program for the primary prevention of PTSD which was tested in a randomised control trial with 12-month follow up.